Does Listening to Music Improve Pain Perception and Anxiety in Patients Undergoing Cystoscopy: A Meta-Analysis - Chen, Guo; Tang, Cai; Liu, Yuebai; Liu, Yuhao; Dai, Yi; Yang, Luo (Frontiers in Surgery, 2021)
Objective: To identify the effect of music on outpatient-based cystoscopy. Methods: We systematically reviewed the effect of music on all reported outpatient for cystoscopy and extracted data from randomized trials from inception to February 3, 2021, with no language restrictions. The analysis was completed via STATA version 14.2. Results: A total of 27 studies were initially identified, and 6 articles containing 639 patients were included in the final analysis. In terms of post-procedural pain perception, a pooled analysis of 6 articles containing 639 patients showed that music seems to improve discomfort in patients who undergo cystoscopy (WMD: −1.72; 95%CI: −2.37 to −1.07). This improvement remained consistent in patients undergoing flexible cystoscopy (FC) (WMD: −1.18; 95% CI: −1.39 to −0.98) and rigid cystoscopy (RC) (WMD: −2.56; 95% CI: −3.64 to −1.48). The music group also had less post-procedural anxiety than those in no music group during cystoscopy (WMD: −13.33; 95% CI: −21.61 to −5.06), which was in accordance with the result of FC (WMD: −4.82; 95% CI: −6.38 to −3.26) than RC (WMD: −26.05; 95% CI: −56.13 to 4.04). Besides, we detected a significantly lower post-procedural heart rate (HR) in the music group than no music group during cystoscopy (WMD: −4.04; 95% CI: −5.38 to −2.71), which is similar to the results of subgroup analysis for FC (WMD: −3.77; 95% CI: −5.84 to −1.70) and RC (WMD: −4.24; 95% CI: −5.98 to −2.50). A pooled analysis of three trials indicated that patients in the music group had significantly higher post-operative satisfaction visual analog scale (VAS) scores than those in the no-music group during RC. However, there was no significant difference between the music group and no music group regarding post-procedural systolic pressures (SPs) during cystoscopy (WMD: −3.08; 95% CI: −8.64 to 2.49). For male patients undergoing cystoscopy, the music seemed to exert a similar effect on decreasing anxiety and pain, and it might serve as a useful adjunct to increase procedural satisfaction. Conclusions: These findings indicate that listening to music contributes to the improvement of pain perception, HR, and anxiety feeling during cystoscopy, especially for male patients undergoing RC. Music might serve as a simple, inexpensive, and effective adjunct to sedation during cystoscopy.